La collection comme lieu de fabrique de la mémoire. L’exemple de Montpellier au xviie siècle - Flore César (Les Cahiers de Framespa)
This article aims to study the dialectic between memory and collectionnism, seen as the phenomenon of collections, and more precisely, from the example of Montpellier in the xviith and xviiith centuries. A first focus interrogates the position of object in collection, as worthy of remembrance and memorial object. A second part enquires the practice of collection as a mnemonic act, the collection can be associated to emblems, and also, seen as a social practice, the collection shall imprinte on the short-term memory. Finally, a last focus studies how collection can be at the service of the collective memory, as a response to a quest of posterity and as a response to filiation.